Micro-fragmented fat injection reduces sepsis-induced acute inflammatory response in a mouse model. (December 2018) - Bouglé, A.; Rocheteau, P.; Hivelin, M.; Haroche, A.; Briand, D.; Tremolada, C.; Mantz, J.; Chrétien, F.
Abstract: Background: Severe sepsis has a high mortality rate. There is increasing evidence that human mesenchymal stem cells possess immunomodulatory properties in sepsis, particularly those from adipose tissue. We hypothesised that micro-fragmented human fat, obtained with minimal alteration of the stromal vascular niche, attenuates the inflammatory response and improves outcome in a murine model of sepsis. Methods: Micro-fragmented fat, lipoaspirate, or saline was administered intraperitoneally 2 h after caecal ligation and puncture (CLP) in C57Bl/6RJ ketamine–xylazine anaesthetised mice. The primary endpoint was the inflammatory score. Secondary endpoints included survival, physiological, histological, and biological parameters. Results: In CLP mice, micro-fragmented fat administration significantly decreased the median (range) inflammatory score compared with saline [17 (14–20) vs 9 (8–12), P =0.006]. Secondary endpoints were also significantly improved in micro-fragmented fat-treated compared with saline-treated CLP mice. Improvement in inflammatory score and in survival was suppressed when micro-fragmented fat was co-administered with liposomes loaded with clodronate (macrophage toxin) or NS-398 (cyclo-oxygenase 2 inhibitor), but not with SC-560 (cyclo-oxygenase 1 inhibitor). Conclusions: In a murine model of severe sepsis, micro-fragmented fat improved early inflammatory status and outcome, at least in part, by a cyclo-oxygenase-2-mediated mechanism. The potential therapeutic value of micro-fragmented fat in severe sepsis warrants further investigation.